Implementasi Enkripsi Advanced Encryption Standard (AES-128) Mode Cipher Block Chaining (CBC) sebagai Keamanan Komunikasi Pergerakan Robot Humanoid KRSBI - Achmad Sudrajat; Yoyok Heru Prasetyo; Mila Kusumawardani (Politeknik Negeri Malang, 2021)
A humanoid robot is a robot that has a human-like shape, which has a body and head, two arms and two legs that allow it to move and interact with the environment created by humans [1]. The humanoid soccer robot system currently used still uses the Robot Operating System (ROS) system, which is basically in the system without any encryption or data security every time communication is made by sending and requesting or what is commonly called Publish and Subscribe. In order to develop the humanoid soccer robot, this research is designed for